2019
DOI: 10.1108/bfj-10-2018-0659
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ concern towards palm oil consumption

Abstract: Purpose Palm oil is a versatile ingredient of many food and non-food products. Yet, over the last year it has rapidly become a controversial product due to its alleged harmful health and environmental effects. Palm oil has rapidly become a controversial product. As a consequence, many food companies have introduced alternative fat sources into their products, in order to meet consumers’ concerns. The purpose of this paper is to: first, investigate consumer purchase intention by assessing whether the environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 70 publications
4
31
3
2
Order By: Relevance
“…We also strive to identify the consequence factor with the strongest influence on consumers to purchase palm oil-free products. To examine this latter aim, Verneau et al [19] have already modeled consumer behavior with the statements we applied, and their research included more indirect relations than what we explored in our current study. That study did not, however, investigate personal beliefs.…”
Section: Aim Of Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…We also strive to identify the consequence factor with the strongest influence on consumers to purchase palm oil-free products. To examine this latter aim, Verneau et al [19] have already modeled consumer behavior with the statements we applied, and their research included more indirect relations than what we explored in our current study. That study did not, however, investigate personal beliefs.…”
Section: Aim Of Researchmentioning
confidence: 99%
“…Sodano et al [16] identified three risk types (health, environmental and social) associated with products containing palm oil. Further research has explored consumer perceptions of these risk types from different perspectives, and how these factors influence purchase intent [3,11,[18][19][20]30,33,34]. Numerous studies have examined specific problems arising during the process of palm oil production [3,11,20,30,33] and only a few were based on the impact of risks perceived in general [18,19,34].…”
Section: Hypotheses 211 Perceived Consequences and Their Impact On Purchase Intentmentioning
confidence: 99%
See 3 more Smart Citations